Inhysningssystem för kalvar och ungdjur i större besättningar - Petersson, Kristin (2008)
In Sweden, there has been a continuous increase in the volume of housing construction for dairy cattle. Since 2004, the number of new, rebuilt and extended dairy cow houses undergoing preliminary inspection by the authorities has grown. The livestock farms have mostly focused on cow units instead of calf and heifer sheds; which has led to a need for information in this area. The purpose of the study was to improve advisors' knowledge about bovine building construction and function; to enable them to provide more qualified advice to conventional and organic milk producers who sustain larger herds. The result of this effort was aimed at the production of healthier calves and heifers.